2022
DOI: 10.1097/bco.0000000000001099
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of automated electronic medical records (EMR) notification to promote provider intervention for severe depression: a retrospective record review

Abstract: Background:Depressive symptoms as measured by the Patient-Reported Outcomes Measurement Information System (PROMIS) Depression (D; PROMIS-D) score is a patient-specific independent predictor of decreased improvement after orthopaedic surgery. Despite evidence that depression predicts worse surgical outcomes, data show orthopaedic surgeons rarely address mental health with their patients. Methods:The authors conducted a retrospective chart review of all patient visit data from October 1, 2018 through December 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Initially, follow-up with patients who screened positive for depression consisted of launching a provider alert that suggested talking points, encouraged primary care physician notification and referral to mental-health, and required documenting actions taken in patients’ Electronic Medical Record (EMR). An early review of alert-efficacy found low adherence with only 29% (N=103) of visits with qualifying PROMIS-D scores reflecting any actions by the treating surgeon 24. In response, department leadership hired a licensed clinical social worker (LCSW) to facilitate follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, follow-up with patients who screened positive for depression consisted of launching a provider alert that suggested talking points, encouraged primary care physician notification and referral to mental-health, and required documenting actions taken in patients’ Electronic Medical Record (EMR). An early review of alert-efficacy found low adherence with only 29% (N=103) of visits with qualifying PROMIS-D scores reflecting any actions by the treating surgeon 24. In response, department leadership hired a licensed clinical social worker (LCSW) to facilitate follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…An early review of alertefficacy found low adherence with only 29% (N = 103) of visits with qualifying PROMIS-D scores reflecting any actions by the treating surgeon. 24 In response, department leadership hired a licensed clinical social worker (LCSW) to facilitate follow-up. The LCSW works to ensure that patients with a positive screen for depressive symptoms are followedup with, assessed, and linked to appropriate mental health or other care.…”
Section: Introductionmentioning
confidence: 99%